Correlation between the Bacteriostatic and Bactericide Effect with Antibiofilm and Anticolony Spreading from Javanese Citronella Oil on Methicillin-Resistant Staphylococcus aureus (MRSA) - Hidayah, Amaliyah Nurul; Wasito, Eddy Bagus; Debora, Kartuti; Basori, Achmad; Isnaeni, Isnaeni; Utomo, Budi (Folia Medica Indonesiana, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogenic bacterium that has been resistant to various types of antibiotics, so it is not easy to be treated with antibiotics and needs other solutions. Javanese citronella oil distilled from the Cymbopogon nardus plant is proven to function as an antibacterial agent (bacteriostatic and bactericidal), fungicide and repellent. This study aimed to prove that there is a positive correlation between bacteriostatic and bactericidal effects with antibiofilm and anticolony spreading from Javanese citronella oil on MRSA. The intended antibiofilm is a barrier to biofilm formation and eradication. Bacteriostatic and antibiofilm effects were tested using microtiter plates assay, bactericidal effect test with subculture into the media and anticolony spreading effect test with spot inoculation in Tryptic Soy Broth media supplemented with 0.24% agar. The bacteriostatic effect test data were analyzed using paired t-test, bactericidal effect using the Friedman test, antibiofilm effect test using Kruskall-Wallis and the results of all the tests correlated using Pearson and Spearman correlation. The statistical significance used was p<0.05. The results showed that Javanese citronella oil had a bacteriostatic concentration of 0.02% (v/v) and bactericidal concentration of 0.78% (v/v). The Pearson correlation test showed that there was a negative correlation between bacteriostatic and bactericidal effects on biofilm formation with r = -0.956 (p = 0.000), but the correlation was positive for biofilm eradication with r = 0.918 (p = 0.000) and anticolony spreading with r = 1.000 (p = 0.000).